The gender gap in earnings losses after job displacement - Hannah Illing; Johannes Schmieder; Simon Trenkle (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
We compare men and women who are displaced from similar jobs by applying an event study design combined with propensity score matching and reweighting to administrative data from Germany. After a mass layo, women's earnings losses are about 35% higher than men's, with the gap persisting five years after displacement. This is partly explained by women taking up more part-time employment, but even women's full-time wage losses are almost 50% higher than men's. Parenthood magnifies the gender gap sharply. Finally, displaced women spend less time on job search and apply for lower-paid jobs, highlighting the importance of labor supply decisions.
Keywords: J16; J63; 330; Job Displacement; Gender Wage Gap; Job Search